Interest Rate Caps The Theory and The Practice - Ferrari, Aurora (The World Bank, 2018)
Ceilings on lending rates remain a widely used policy tool that is intended to lower the overall cost of credit or protect consumers from exorbitant rates. Interest rate caps come in many forms and scopes and, according to their rationale, ceilings can affect a small segment or the overall market. Over the past years, many countries have introduced new or tightened existing restrictions, while only a few have removed or eased them. This paper takes stock of recent developments in interest rates caps globally and classifies them according to a novel taxonomy. The paper also presents six case studies of different types of interest rate caps. The case studies indicate that while some forms of interest rate caps can indeed reduce lending rates and help to limit predatory practices by formal lenders, interest rate caps often have substantial unintended side-effects. These side-effects include increases in non-interest fees and commissions, reduced price transparency, lower credit supply and loan approval rates for small and risky borrowers, lower number of institutions and reduced branch density, as well as adverse impacts on bank profitability. Given these potential negative consequences of interest rate caps, the paper discusses alternatives to reduce the cost of credit